Utilizing GO/PEDOT:PSS/PtNPs-enhanced high-stability microelectrode arrays for investigating epilepsy-induced striatal electrophysiology alterations - Han, Meiqi; Wang, Yu; Jing, Luyi; Yang, Gucheng; Liu, Yaoyao; Mo, Fan; Xu, Zhaojie; Luo, Jinping; Jia, Qianli; Zhu, Yuxin; Cao, Hanwen; Cai, Xinxia; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
The striatum plays a crucial role in studying epilepsy, as it is involved in seizure generation and modulation of brain activity. To explore the complex interplay between the striatum and epilepsy, we engineered advanced microelectrode arrays (MEAs) specifically designed for precise monitoring of striatal electrophysiological activities in rats. These observations were made during and following seizure induction, particularly three and seven days post-initial modeling. The modification of graphene oxide (GO)/poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS)/platinum nanoparticles (PtNPs) demonstrated a marked reduction in impedance (10.5±1.1kΩ), and maintained exceptional stability, with impedance levels remaining consistently low (23kΩ) even 14 days postimplantation. As seizure intensity escalated, we observed a corresponding increase in neuronal firing rates and local field potential power, with a notable shift towards higher frequency peaks and augmented inter-channel correlation. Significantly, during the grand mal seizures, theta and alpha bands became the dominant frequencies in the local field potential. Compared to the normal group, the spike firing rates on day 3 and 7 post-modeling were significantly higher, accompanied by a decreased firing interval. Power in both delta and theta bands exhibited an increasing trend, correlating with the duration of epilepsy. These findings offer valuable insights into the dynamic processes of striatal neural activity during the initial and latent phases of temporal lobe epilepsy and contribute to our understanding of the neural mechanisms underpinning epilepsy.